A comparison of running economy across seven highly cushioned racing shoes with carbon-fibre plates. (4th May 2022) - Joubert, Dustin P.; Jones, Garrett P.
Abstract: Recent advancements in running shoe technology, particularly in the Nike Vaporfly, have been shown to improve running economy. Other brands have now also developed new, advanced shoes with thicker midsole foams intended to be more compliant and resilient, along with a carbon-fibre plate. However, none of these new shoes have been compared to the Vaporfly in terms of running economy. Therefore, we compared running economy among seven different highly cushioned racing shoes with a carbon plate: Hoka Rocket X (Hoka RX), Saucony Endorphin Pro (Saucony EP), Nike Alphafly (Nike AF), Asics Metaspeed Sky (Asics MS), Nike Vaporfly Next % 2 (Nike VF2), New Balance RC Elite (New Bal RC), Brooks Hyperion Elite 2 (Brooks HE2) and 1 traditional racing shoe: Asics Hyperspeed (Asics HS) in twelve male runners (5k best: 16.0 ± 0.7 min) during two lab visits. Shoes were tested in a random sequence over 8 × 5-min trials (16 km·h −1 ; 5-min rest between trials) on visit 1, and in the reverse/mirrored order for visit 2. Metabolic and running mechanics data were collected and averaged across visits. V̇O2 (ml·kg −1 ·min −1 ; % change from Asics HS) was significantly different across shoes. Hoka RX (51.67 ± 2.07) and Brooks HE2 (51.42 ± 1.72) did not differ from Asics HS (51.71 ± 2.02). While Saucony EP (50.93 ± 1.82; −1.48 ± 0.72%) and New Bal RC (50.99 ± 1.83; −1.37 ± 0.78%) were statistically better than Asics HS, they were inferior to Nike AF (50.13 ± 1.86; −3.03 ± 1.48%), Nike VF2 (50.29 ± 1.72; −2.72 ± 1.02%), and Asics MS (50.39 ± 1.71; −2.52 ± 1.08%). From these data, it appears most running shoe companies have not yet caught up to the advantages conferred by the Nike VF2.